Engineering on the surprise continuum as applied to software practice. - Riehle, Richard (Software engineering notes.)
Speakers at conferences often mention the Principle of Least Surprise. This article explores the notion of surprise on a Surprise Tolerance Continuum. We also comment on how different disciplines benefit from managing surprise. Since this publication deals with software engineering, we focus on problems related to the creation, management, and maintenance of software.